“I’m pulling through because of you”: injured workers’ perspective of workplace factors supporting return to work under the Saskatchewan Workers’ Compensation Board scheme - Lewis, Ian; Houdmont, Jonathan (Frontiers in Rehabilitation Sciences, 2024)
Background Research demonstrates sustained return to work (RTW) by individuals on medical leave is influenced by personal and job resources and job demands. Relatively few studies have been conducted in the workers’ compensation context that is known to have longer absence durations for RTW. Aims This study sought to illuminate workers’ experience as they returned to work following a work injury that was either psychological in nature or involved more than 50 days of disability, with a focus on the co-worker, supervisor, and employer actions that supported their return. Methods Workers in Saskatchewan, Canada, with a work-related psychological or musculoskeletal injury, subsequent disability, and who returned to work in the last three years, were invited to complete an online survey comprising of free-text questions. Thematic analysis was used to explore participants’ experiences. Results Responses from 93 individuals were analysed. These revealed that persistent pain, emotional distress, and loss of normal abilities were present during and beyond returning to work. Almost two-thirds indicated that the supervisors’ and co-workers’ support was critical to a sustained return to work: their needs were recognized and they received autonomy and support to manage work demands. By contrast, one-third indicated that the support they expected and needed from supervisors and employers was lacking. Conclusions Workers returning to work lacked personal resources but co-workers’ and supervisors’ support helped improve confidence in their ability to RTW. Supervisors and employers should acknowledge workers’ experiences and offer support and autonomy. Likewise, workers can expect challenges when returning to work and may benefit from cultivating supportive relationships with co-workers and supervisors.